2010
DOI: 10.1200/jco.2009.22.6043
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic and Pharmacoproteomic Studies of Cetuximab in Metastatic Colorectal Cancer: Biomarker Analysis of a Phase I Dose-Escalation Study

Abstract: Biomarker analysis supported the functional equivalence of weekly and every second week administration of cetuximab and provided further confirmation that patients with KRAS wild-type mCRC were those most likely to benefit from cetuximab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 32 publications
5
60
0
Order By: Relevance
“…The predictive value of EREG and AREG expression for cetuximab sensitivity was confirmed by Jacobs and colleagues, which analyzed primary tumors from refractory patients with mCRC treated with cetuximab-based therapies (46). Furthermore, in the 045 phase I study of cetuximab monotherapy as first-line treatment of patients with mCRC, Tabernero and colleagues found that AREG and EREG mRNA levels were significantly higher in tumor samples from patients with clinical response to cetuximab as compared with patients with disease progression (47). Although high level of expression of AREG and EREG ligands may predict a better response to treatment with cetuximab in patients with mCRC, HB-EGF and TGF-a overexpression could confer lack of sensitivity to EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The predictive value of EREG and AREG expression for cetuximab sensitivity was confirmed by Jacobs and colleagues, which analyzed primary tumors from refractory patients with mCRC treated with cetuximab-based therapies (46). Furthermore, in the 045 phase I study of cetuximab monotherapy as first-line treatment of patients with mCRC, Tabernero and colleagues found that AREG and EREG mRNA levels were significantly higher in tumor samples from patients with clinical response to cetuximab as compared with patients with disease progression (47). Although high level of expression of AREG and EREG ligands may predict a better response to treatment with cetuximab in patients with mCRC, HB-EGF and TGF-a overexpression could confer lack of sensitivity to EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Although high level of expression of AREG and EREG ligands may predict a better response to treatment with cetuximab in patients with mCRC, HB-EGF and TGF-a overexpression could confer lack of sensitivity to EGFR inhibitors. In fact, in 045 clinical trial, TGF-a mRNA levels were significantly elevated in the tumors from patients with mCRC with disease progression after cetuximab therapy as compared with patient with clinical response (47). Furthermore, increased HB-EGF may be correlated with cetuximab resistance in head and neck squamous cell carcinoma (48).…”
Section: Discussionmentioning
confidence: 98%
“…The clinical antitumor activity seen with Sym004 is in line with the superior antitumor activity of Sym004 over cetuximab in preclinical animal models of acquired cetuximab resistance ( 7 , 17 ). In addition, we showed here that Sym004 is highly effi cient at blocking colorectal cancer cell line growth in the presence of the high-affi nity ligands EGF and TGFα, factors known to be both upregulated in response to anti-EGFR antibody treatment and determinants of EGFR inhibitor resistance ( 13 ). We further hypothesize that the pharmacodynamic effects of Sym004, with sustained decrease in EGFR expression in tumor biopsies, relate to the ability of the mAbs to cross-link the EGFR, causing internalization and subsequent degradation of the antibody-receptor complexes ( 17 ).…”
Section: Research Articlementioning
confidence: 81%
“…mCRC patients with a higher gene expression of EREG and AREG prior to treatment tend to have better disease control by cetuximab than low expressers (12). On the other hand, mCRC patients with disease progression have elevated TGFa (13). An increased expression of high-affinity ligands, such as TGFa and HB-EGF, was also observed in a mouse colorectal cancer model with acquired resistance to cetuximab (14).…”
Section: Introductionmentioning
confidence: 89%